Dinamika Pagang Gadai sebagai Relasi Ekonomi Petani di Minangkabau, Sumatera Barat - Yetty Oktayanty; Mutia Kahanna; Hijratur Rahmi; Divani Fadhilah Putri; Maskota Delfi (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2026)
This article examines the practice of pagang gadai as a socio- economic relation among rural peasants in Minangkabau, West Sumatra. The research aims to analyze pagang gadai not merely as a customary land-based lending mechanism, but as a transforming relation of production that reflects changing patterns of access, control, and ownership over the means of production. Using Karl Polanyi’s concept of embeddedness and Karl Marx’s historical materialism, this article argues that pagang gadai has shifted from a solidaristic mechanism rooted in kinship and customary values into a semi-capitalist relation that reproduces class inequality between panggadai (landowners/ debtors) and pamagang (lenders/ creditors). This research employs a qualitative method with a descriptive approach. Data were collected through field observations, in-depth interviews, and documentation in rural peasants household in Minangkabau. The findings demonstrate that, despite being socially contested, pagang gadai continues to function as an alternative source of credit for peasants facing limitied access to formal financial institutions and agricultural capital. However, the practice simultaneously contributes to the temporary loss of peasants’ control over pusako tinggi (ancestral land), enabling the accumulation of agricultural surplus through control over land and unequal bargaining relations. The research highlights the contradiction between customary values of solidarity and the increasing commodification of ancestral land within contemporary rural economic relations.